Whole lung lavage for pulmonary alveolar proteinosis: still the most up-to-date treatment - YILDIZELİ, BEDRETTİN; CEYHAN, BERRİN; BEKİROĞLU, GÜLNAZ NURAL; KARAKURT, SAİT; ÇELİKEL, TURGAY HÜSEYİN; LAÇİN, TUNÇ (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2017)
Background: This study aims to evaluate the significance of whole lung lavage on prelavage and postlavage blood gas analysis values of patients with pulmonary alveolar proteinosis. Methods: Data of nine patients (1 male, 8 females; mean age 38.2 years; range 29 to 60 years) who were diagnosed to have pulmonary alveolar proteinosis with interventional techniques between January 1998 and May 2010 at Marmara University Hospital Department of Thoracic Surgery were reviewed. Patients' prelavage pulmonary function tests, pre-and postlavage blood gas analyses, and radiologic images were evaluated. Restrictive ventilatory pattern and impaired gas exchange were detected and whole lung lavage was performed in all patients. Results: No major complications were observed during whole lung lavage. Each lung was washed with 15-30 L of physiological saline solution. Patients were followed-up in the intensive care unit intubated for a mean of 2.6 days (range, 1 to 16 days). Mean duration of stay at intensive care unit was 3.5 days (range, 1-16 days). One patient died 16 days after her fifth lavage due to respiratory arrest during an attempt for percutaneous tracheostomy. Increment of the postlavage partial pressures of oxygen and oxygen saturations was statistically significant. All patients showed subjective improvement. Conclusion: Our experience suggests that whole lung lavage is a safe technique when strict adherence to lavage protocol is maintained. Postlavage symptomatic relief is rapid and oxygenation improves significantly.
Keywords: Hypoxia; pulmonary alveolar proteinosis; whole lung lavage; BRONCHOALVEOLAR LAVAGE; SERUM; PATHOGENESIS; DEFICIENCY; PATIENT; FLUID